1995
DOI: 10.1016/s0969-2126(01)00224-6
|View full text |Cite
|
Sign up to set email alerts
|

Hydration structure of a collagen peptide

Abstract: The roles of hydroxyproline and hydration are strongly interrelated in the structure of the collagen triple helix. The specific, repetitive water bridges observed in this structure buttress the triple-helical conformation. The extensively ordered hydration structure offers a good model for the interpretation of the experimental results on collagen stability and assembly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

38
570
1
4

Year Published

1998
1998
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 582 publications
(613 citation statements)
references
References 41 publications
38
570
1
4
Order By: Relevance
“…Indeed, a canonical structural water molecule (30) is predicted to be present in an appropriate position on the trailing chain, bound between the peptide carbonyl group of G22 and the hydroxyl group of O24. Collagen triple helices are highly hydrated (30) and other structural water molecules may also contribute to the SPARCcollagen interaction.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, a canonical structural water molecule (30) is predicted to be present in an appropriate position on the trailing chain, bound between the peptide carbonyl group of G22 and the hydroxyl group of O24. Collagen triple helices are highly hydrated (30) and other structural water molecules may also contribute to the SPARCcollagen interaction.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, they do not seem to be small enough to penetrate the nanometric voids between collagen molecules within the demineralized collagen fibers. 50 Moreover, it has been shown that collagen molecules are surrounded by water molecules to form highly ordered and multilayered cylinders of hydration 51 which may favor the hydrolytic degradation of resin monomers in a sub-micrometer level.…”
Section: Why Do Adhesive Interfaces Fail?mentioning
confidence: 99%
“…21,22 These hydrogen bonded networks often adopt pentagonal arrangements of water and are anchored to the peptide chain through backbone carbonyls and hydroxyl groups of Hyp ( Figure 1a). The observation of Hyp involvement in a hydrogen-bonded water network is consistent with that proposed by Ramachandran's group on the basis of modeling and Privalov on the basis of calorimetry studies on collagens.…”
Section: X-ray Crystallography Of Triple-helical Peptidesmentioning
confidence: 99%